2019
DOI: 10.3389/fmicb.2019.01853
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Porcine Viruses by Different Cell-Targeted Antiviral Drugs

Abstract: Antiviral compounds targeting cellular metabolism instead of virus components have become an interesting issue for preventing and controlling the spread of virus infection, either as sole treatment or as a complement of vaccination. Some of these compounds are involved in the control of lipid metabolism and/or membrane rearrangements. Here, we describe the effect of three of these cell-targeting antivirals: lauryl gallate (LG), valproic acid (VPA), and cerulenin (CRL) in the multiplication of viruses causing i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…We previously described the efficient inhibition of virus multiplication in several cell lines in the presence of a host-targeted AV, the antioxidant food additive LG ( 19 , 20 ). We also demonstrated that VPA, another drug affecting cellular functions, used for treatment of neurological disorders, caused a drastic reduction in replication of all enveloped viruses tested ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously described the efficient inhibition of virus multiplication in several cell lines in the presence of a host-targeted AV, the antioxidant food additive LG ( 19 , 20 ). We also demonstrated that VPA, another drug affecting cellular functions, used for treatment of neurological disorders, caused a drastic reduction in replication of all enveloped viruses tested ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Esters of G have also been reported to inhibit the proliferation of tumoral cell lines ( 13 ) by triggering the apoptosis of the cell ( 14 ) and the concomitant inhibition of protein tyrosine kinases ( 15 ) and have been described as AVs ( 16 18 ). We have previously reported that LG can inhibit the replication in cultured cells of African swine fever virus (ASFV), foot-and-mouth disease virus (FMDV), herpesvirus simplex (HSV-I), influenza virus, Sindbis virus (SINV), vaccinia virus (VACV), vesicular stomatitis virus (VSV), swine vesicular disease virus (SVDV), and transmissible gastroenteritis virus (TGEV), also reducing mortality and FMDV load in vivo in a mouse model ( 19 , 20 ). The antiviral effect of LG might be mediated by its interaction with phospholipids in biological membranes ( 21 ), with surfactant effects destabilizing the cellular and viral envelopes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, much effort has been made to discover and study antiviral agents against ASFV [42][43][44][45][46][47]. However, none of the described compounds have been tested in vivo yet, thereby highlighting the need to search for new antiviral agents targeted towards the ASFV.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the 4D docking experiments and MD simulations revealed that this compound could interact with the taxane site in the same manner as many other microtubules stabilizing agents [50]. Ethyl [(4-cyano-1-phenyl-5,6,7,8-tetrahydroisoquinolin-3-yl) The immunostaining of ASFV-pI215L and ASFV-infected cells were achieved by incubation with two in-house primary antibodies: mouse anti-ASFV-PI215L and anti-ASFV swine serum directly conjugated to fluorescein isothiocyanate (FITC; 1:100, 1 h, RT) as previously described [47,48]. The affinity purified Alexa Fluor 568-conjugated goat anti-mouse secondary antibody In some experiments, ASFV-infected cells were exposed to EdU (5-ethynyl-2′-deoxyuridine; 25 microM) for 15 min before collection; cells exposed to solvent (DMSO) served as controls.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative that remains under study is valproic acid (VPA) [26], a branched, shortchain fatty acid used in the treatment of seizure disorders [27]. Numerous studies have proven that VPA interferes with the infectious cycle of several enveloped viruses, including herpesviruses, flaviviruses, arenaviruses, poxviruses, picornaviruses, rhabdoviruses, and coronaviruses, among others [28][29][30][31][32][33]. However, VPA shows hepatotoxic and teratogenic activity [34], and thus to reduce these deleterious effects, derivatives of VPA have been tested.…”
Section: Introductionmentioning
confidence: 99%